Importance of the Ultrasound Probe Angle on the Rotation Fill-In Signature in Ultrasound Axial-Shear Strain Imaging - Galaz-Donoso, B (Elsevier Inc., 2021)
The rotation fill-in is a signature of tumor benignity in rotation elastograms and has been used for breast tumor classification. It is a consequence of the bonding condition at the tumor–tissue interface. In vivo studies have revealed the presence of fluctuations when inclined uniaxial external compression is applied. However, the physical meaning of these fluctuations is not yet fully understood. In this article we present an experimental and numerical study of the rotation fill-in signature as a function of the probe s tilt angle. This angle introduces asymmetries in the stress field, modifying the bonding condition. We numerically consider this asymmetry by using a model of friction with a simple angular dependence, which allows us to capture the experimental trends. We argue that the formulation of a tumor model with a bonding condition dependence may have potential implications in correct tumor classification. © 2020 World Federation for Ultrasound in Medicine & Biology